Makrofungi Resisten Merkuri (Hg) - Cut Kandy Safiera; Aceng Ruyani; Sipriyadi; Bhakti Karyadi; Deni Parlindungan; Khairunnisa (Universitas PGRI Silampari, 2024)
This study aims to identify types of macrofungi that are resistant to the presence of Hg in their environment. The method used is survey research by exploring mushrooms in the area around the Small Scale Gold Mining (ASGM). Tambang Sawah Village, Lebong Regency, Bengkulu Data findings were analyzed by descriptive qualitative. The results showed that the types of macrofungi that were able to survive Hg stress were Ganoderma applanatum, Dacryopinax spathularia, Daldinia concentrica, Ganoderma lucidum and Polyporus alveolaris. In conclusion, five types of macrofungi that are adaptive to mercury (Hg) were found. The highest Hg accumulation was found in D. concentrica.